Integrating energy governance and environmental justice: Role of renewable energy. (December 2022) - Govindarajan, Hari Krishnan; Ganesh, L.S.
Abstract: Energy and Environmental Justice is a well-researched subject. Research points to close interactions among energy, economy, sustainability, and policy aspects that lead to several policy issues of energy governance and environmental justice. Renewable energy promotion and the transition to a low carbon economy in all nations necessitate the integration of the complex nature of energy governance and environmental justice issues and their interactions. For the integration, we present a Morphological Analysis framework consisting of 6 dimensions and 25 variants that can be effectively used by policymakers in different nations to guide their transition to a low carbon economy via renewable energy. Presently, we can observe that environmental justice is largely restricted to justice literature. However, a holistic study of environmental justice requires among others a renewed research focus on new energy governance issues arising out of the concern to ensure justice globally all along by deploying renewable energy systems for the "just" transition to low carbon sources. We also highlight immediate research opportunities arising from the integration.